PENGARUH CONSERVATISM, TRANSFER PRICING, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Iftikhor, Adelia Nur; Indriasih, Dewi; Fajri, Aminul (Politeknik Negeri Ambon, 2025)
Introduction: The purpose of this study is to investigate experimentally how capital intensity, transfer pricing, and conservatism affect tax evasion in the food and beverage industry of the Indonesia Stock Exchange-listed manufacturing companies between 2020 and 2024.Methods: This study used a dataset and a quantitative methodology. The sample consisted of companies that produce food and beverages and are traded on the Indonesian Stock Exchange between 2020 and 2024. The purposeful sampling method was employed, and 37 businesses in met the selection requirements. The data analysis method used in this study was multiple linear regression.Results: According to this analysis, tax evasion in the food and beverage subsector listed on the Indonesia Stock Exchange from 2020 to 2024 was negatively impacted by conservatism, transfer pricing had a positive impact on tax avoidance, but capital intensity did not affect tax avoidance. From 2020 to 2024, capital intensity had little bearing on tax evasion in food and beverage manufacturing firms listed on the Indonesia Stock Exchange (IDX). To compare the findings with those of this study, future research is expected to use alternative factors or include variables that can affect tax evasion, such as company size, profitability, or leverage. Additionally, the research term or the research object may be extended. Keywords.: Capital Intensity, Conservatism, Tax Avoidance, Transfer Pricing